HETEROGENEITY OF CHANGES IN THE CAPILLARY BED OF DIFFERENT AREAS OF THE ADRENAL GLANDS DURING ADAPTATION TO HYPOBARIC HYPOXIAHETEROGENEITY OF CHANGES IN THE CAPILLARY BED OF DIFFERENT AREAS OF THE ADRENAL GLANDS DURING ADAPTATION TO HYPOBARIC HYPOXIA (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The study was conducted on male laboratory rats. Hypobaric hypoxia was modeled by rarefaction of air in a pressure chamber simulating ascents to a height of 6000-6500 m above sea level. Hypoxic effects on the body were carried out for 1,3,7,15,30 days. It was found that throughout the experiment, the morphometric parameters of the intra-border microhemocirculatory bed of the adrenal glands were increased in all areas of the cortex and in the medulla, but the vascular bed in the bundle and mesh zones underwent the greatest changes, which indicates the presence of zonality in the organ's response to oxygen starvation of tissues.
Keywords: hypobaric hypoxia, rats, adaptation, adrenal gland, capillaries.